Digital media and the Greek crisis : cyberconflicts, discourses and networks - Ferra, Ioanna (Digital activism and society., 2019)
This book concentrates on the parallel evolution of debt crisis and digital communications in Greece. By examining four different online and social media platforms, it examines a seven-year period to uncover the impact of digital media on the contentious politics of crisis, as well as the impact of the political economic sphere on the formation of the Greek digital mediascape. The research employs cyberconflict theory to situate online mediated conflict in a geo-political, socio-political and historical context, revealing the dynamic relation between the online media and the offline world. The work provides an updated framework which recommends the use of online data and the study of social media platforms for the examination of cyberconflict. It delves into the political transformations which have emerged in the context of the Greek crisis such as the anti-/pro- austerity debate, the euro-vs-drachma debate, the anti-/pro-governmental debate, or the Grexit discussion, and shines a light on how, in the context of crisis, the online space becomes a magnifying glass which points out conflict, opposition and drives polarization.